Financial Distress Analysis Using the Ohlson Model in Indonesian State Owned Enterprises - Krismularso Seno Pamungkas (Journal of Accounting and Finance Management, 2023)
This study aims to analyze financial distress conditions using the Ohlson financial distress model in SOEs Non-Financial Sector for the 2017-2020 financial year performance period. The object of analysis is non-financial and banking SOEs registered under Ministry of SOEs. The results of the study are: 1) The aggregate probability of default for all SOEs has increased from 2017 to 2020; 2) the highest increase is the Probability of Default in 2020 compared to the Probability of Default in 2019; 3) SOEs in the Tourism Sector are the sectors that experience the most financial distress in 2020, while the Plantation and Forestry sector are the least financial distress in 2020; 4) SOEs in the same sector may show a different trend of increasing/decreasing Probability of Default.